The impact of agricultural support and protection subsidy policy on grain production efficiency: A case study of China - Yuan Tian; Yuxi Zhou (PLoS ONE, 2025)
Based on panel data from 31 Chinese provinces from 2012 to 2022, this study employs a difference-in-difference method to assess the impact of the agricultural support and protection subsidy (ASPS) policy on grain production efficiency. The results indicate that the ASPS policy has a significant positive impact on grain production efficiency, and the results remain robust through multiple robustness tests. Furthermore, heterogeneity analysis reveals that the policy’s impact varies substantially across different regions and types of grain crops. Mechanism analysis further demonstrates that the ASPS policy enhance grain production efficiency by improving the grain cultivation areas and productive inputs. Consequently, we propose targeted policy recommendations, including enhancing the intensity and precision of subsidies, implementing differentiated subsidy approaches, and utilizing subsidies to stimulate dual efficiencies in both scale and investment.